Kemampuan Menulis Slogan Pada Siswa Kelas VIII SMP Negeri 10 Kupang - Tanesib, Apmida; Margareta, Karus M.; Nurhuda, Aris (Jurnal Lazuardi, 2025)
This study is entitled “The Ability to Write Slogans Among Eighth Grade K Students of SMP Negeri 10 Kupang”. The purpose of this research is to describe the ability of eighth grade K students at SMP Negeri 10 Kupang in writing slogans. The theoretical framework used in this study includes writing theory and constructivist learning theory. This research employed a qualitative descriptive method. Data collection techniques included observation, testing/evaluation, and documentation study. Based on the research conducted on February 24, 2025, involving 27 students from class VIII-K of SMP Negeri 10 Kupang, it was found that the majority of students were able to write slogans well. Of the total, 25 students (92.6%) achieved scores above the Minimum Mastery Criteria (KKTP), which is ≥75, while only 2 students (7.4%) did not meet the criteria. Therefore, it can be concluded that the slogan writing ability of class VIII-K students is categorized as very good, as most students met or exceeded the school’s minimum passing score (≥75). These results indicate that, in general, class VIII-K students are highly capable of writing slogans that align with the assessment criteria, including diction usage, sentence structure, and relevance to the theme.